Green Light to Plant Responses to Pathogens: The Role of Chloroplast Light-Dependent Signaling in Biotic Stress - Delprato, María Laura (2015)
Light has a key impact on the outcome of biotic stress responses in plants by providing most of the energy and many signals for the deployment of defensive barriers. Within this context, chloroplasts are not only the major source of energy in the light; they also host biosynthetic pathways for the production of stress hormones and secondary metabolites, as well as reactive oxygen species and other signals which modulate nuclear gene expression and plant resistance to pathogens. Environmental, and in particular, light-dependent regulation of immune responses may allow plants to anticipate and react more effectively to pathogen threats. As more information is gathered, increasingly complex models are developed to explain how light and reactive oxygen species signaling could interact with endogenous defense pathways to elicit efficient protective responses against invading microorganisms. The emerging picture places chloroplasts in a key position of an intricate regulatory network which involves several other cellular compartments. This article reviews current knowledge on the extent and the main features of chloroplast contribution to plant defensive strategies against biotic stress.